HERC5 E3 ligase mediates ISGylation of hepatitis B virus X protein to promote viral replication. (18th October 2021) - Bawono, Rheza Gandi; Abe, Takayuki; Qu, Mengting; Kuroki, Daisuke; Deng, Lin; Matsui, Chieko; Ryo, Akihide; Suzuki, Tetsuro; Matsuura, Yoshiharu; Sugiyama, Masaya; Mizokami, Masashi; Shimotohno, Kunitada; et al.
Abstract : Ubiquitin and ubiquitin-like protein modification play important roles in modulating the functions of viral proteins in many viruses. Here we demonstrate that hepatitis B virus (HBV) X protein (HBx) is modified by ISG15, which is a type I IFN-inducible, ubiquitin-like protein; this modification is called ISGylation. Immunoblot analyses revealed that HBx proteins derived from four different HBV genotypes accepted ISGylation in cultured cells. Site-directed mutagenesis revealed that three lysine residues (K91, K95 and K140) on the HBx protein, which are well conserved among all the HBV genotypes, are involved in acceptance of ISGylation. Using expression plasmids encoding three known E3 ligases involved in the ISGylation to different substrates, we found that HERC5 functions as an E3 ligase for HBx-ISGylation. Treatment with type I and type III IFNs resulted in the limited suppression of HBV replication in Hep38.7-Tet cells. When cells were treated with IFN-α, silencing of ISG15 resulted in a marked reduction of HBV replication in Hep38.7-Tet cells, suggesting a role of ISG15 in the resistance to IFN-α. In contrast, the silencing of USP18 (an ISG15 de-conjugating enzyme) increased the HBV replication in Hep38.7-Tet cells. Taken together, these results suggest that the HERC5-mediated ISGylation of HBx protein confers pro-viral functions on HBV replication and participates in the resistance to IFN-α-mediated antiviral activity.